2018
DOI: 10.1111/ffe.12924
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack propagation behaviour of RC beams strengthened with prestressed CFRP under cyclic bending loads

Abstract: Numerical and experimental methods were applied to investigate the fatigue crack propagation behaviour of the reinforced concrete (RC) beams strengthened with prestressed carbon fibre laminate (CFL). On the one hand, a theoretical analysis method was presented to calculate the stress intensity factor K of the main crack on RC beam strengthened with prestressed CFL. On the other hand, fatigue crack propagation tests were carried out to obtain the crack propagation rate on RC beams strengthened with CFL, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…[18][19][20][21][22] It is found that interfacial fatigue life can be expressed by some other parameters such as the stress intensity factor for the interfacial fatigue cracks, interfacial shear stress and residual strains at the edge of concrete compression zone. [23][24][25] Moreover, the stress level of the reinforcing steel is critical in predicting fatigue life of FRP strengthened RC beams. 26 The first loading cycle dissipates more energy than any other cycle through cracking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22] It is found that interfacial fatigue life can be expressed by some other parameters such as the stress intensity factor for the interfacial fatigue cracks, interfacial shear stress and residual strains at the edge of concrete compression zone. [23][24][25] Moreover, the stress level of the reinforcing steel is critical in predicting fatigue life of FRP strengthened RC beams. 26 The first loading cycle dissipates more energy than any other cycle through cracking.…”
Section: Introductionmentioning
confidence: 99%
“…In the research of constant amplitude fatigue loading, the types of fiber and concrete, the form of FRP, the method of bonding, the scheme of loading, the size effect and the service environment have a great influence on the fatigue life 18–22 . It is found that interfacial fatigue life can be expressed by some other parameters such as the stress intensity factor for the interfacial fatigue cracks, interfacial shear stress and residual strains at the edge of concrete compression zone 23–25 . Moreover, the stress level of the reinforcing steel is critical in predicting fatigue life of FRP strengthened RC beams 26 .…”
Section: Introductionmentioning
confidence: 99%